Strategic Planning and Organization Performance: A Review on Conceptual and Practice Perspectives - Jayawarna, Sahan (Archives of Business Research, 2019)
Strategic planning has been an integral part of organizations while its impact on organization performance has been debated for many years. There are mixed (positive and negative) results for strategic planning and performance relationship whist most of the studies were done in organizations in developed countries. However recent research studies argue that it is equally important to identify internal and external factors affecting strategic planning and performance relationship as previous researches were limited to finding directional relationship. Researchers argue that future research should shift from a focus on “does planning lead to performance?” to “how, when, and why does strategic planning lead to performance?” Since there are limited strategic planning research studies in Sri Lankan context, paper concludes propositions for future research in line with empirical justifications.